2019
DOI: 10.1029/2019jg005094
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐Sensitive Controls on Large Spring Emissions of CH4 and CO2 From Northern Lakes

Abstract: Northern lakes are important sources of the climate forcing trace gases methane (CH4) and carbon dioxide (CO2). A substantial portion of lakes' annual emissions can take place immediately after ice melt in spring. The drivers of these fluxes are neither well constrained nor fully understood. We present a detailed carbon gas budget for three subarctic lakes, using 6 years of eddy covariance and 9 years of manual flux measurements. We combine measurements of temperature, dissolved oxygen, and CH4 stable isotopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 102 publications
8
101
0
Order By: Relevance
“…This study only considered ebullition fluxes of CH 4 , and there are no studies comparing Δ 18 with 14 C or flux for dissolved CH 4 . Where comparison is possible, dissolved CH 4 tends to contain younger carbon than ebullition CH 4 (Elder et al, 2019) and is more likely to have its stable isotope composition influenced by methane oxidation (Elder et al, 2019;Jansen et al, 2019). Further study will be needed to assess whether the patterns observed here for ebullition CH 4 also apply to diffusive CH 4 fluxes.…”
Section: 1029/2019gl086756mentioning
confidence: 89%
See 1 more Smart Citation
“…This study only considered ebullition fluxes of CH 4 , and there are no studies comparing Δ 18 with 14 C or flux for dissolved CH 4 . Where comparison is possible, dissolved CH 4 tends to contain younger carbon than ebullition CH 4 (Elder et al, 2019) and is more likely to have its stable isotope composition influenced by methane oxidation (Elder et al, 2019;Jansen et al, 2019). Further study will be needed to assess whether the patterns observed here for ebullition CH 4 also apply to diffusive CH 4 fluxes.…”
Section: 1029/2019gl086756mentioning
confidence: 89%
“…Further study will be needed to assess whether the patterns observed here for ebullition CH 4 also apply to diffusive CH 4 fluxes. However, for the studied lakes, ebullition fluxes are estimated to be the dominant source of CH 4 emissions in the ice-free season (Jansen et al, 2019;Sepulveda-Jauregui et al, 2015).…”
Section: 1029/2019gl086756mentioning
confidence: 94%
“…Q eff (W m −2 ) represents the net heat flux into the mixing layer and is the sum of net shortwave and long-wave radiation and sensible and latent heat fluxes. Penetration of radiation into the water column was evaluated across seven wavelength bands via Beer's law (Jellison and Melack, 1993). An attenuation coefficient of 0.74 was computed for the visible portion of the spectrum from Secchi depth (2.3 m; Karlsson et al, 2010) following Idso and Gilbert (1974).…”
Section: Computing Gas Transfer Velocities With the Surface Renewal Mmentioning
confidence: 99%
“…Ebullition moves CH 4 rapidly from sediments directly to the atmosphere, typically bypassing microbial CH 4 oxidation in the water column 11 . Incoming short-wave radiation and sediment temperature have been identified as strong predictors of ebullitive CH 4 emission from sub-arctic post-glacial lakes on an annual basis, with higher temperature increasing emissions during the ice-free season 2,12 . However, the extent and drivers of spatial variability in this temperature response, particularly within lakes, are poorly understood.…”
Section: Main Textmentioning
confidence: 99%
“…These lakes are part of the Stordalen Mire complex, a hydrologically interconnected, discontinuous permafrost ecosystem encompassing post-glacial lakes and a mosaic palsa/wetland in approximately equal portions 13 . The lakes contribute ∼55% of the total ecosystem CH 4 loss 2 and are model sites for studying ebullitive emissions, which were collected at lake surfaces for the six summers from 2009-2014 12,14 every 1-3 days 9 . Here, we linked site-specific (lake edge vs. middle) CH 4 emissions to analyses of the microbiota and biogeochemistry in the underlying sediments.…”
Section: Main Textmentioning
confidence: 99%